2013
DOI: 10.1521/jsyt.2013.32.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Applying Resistance Theory to Depression in Black Women

Abstract: Depression in African American women is often invisible, misdiagnosed, and ineptly treated. Black women are vulnerable to depression due to chronic environmental stressors of racism, sexism, poverty, cultural socialization practices, and social health difficulties. Middle-class and college-educated Black women are also vulnerable to depression, although less of the research has focused on this segment of Black women. We highlight psychological literature that explores the phenomenon of depression among Black w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Suboptimal resistance is associated with short-term and/or pleasure inducing strategies (e.g., comfort eating and drinking) that offer immediate gratification and are soothing, but do not serve people well in the long run. Specifically, suboptimal resistance is associated with increased vulnerability to and poor health outcomes, such as obesity, diabetes, heart disease, and addiction (Martin, Boadi, Fernandes, Watt, & Robinson-Wood, 2013; Robinson & Ward, 1991; Robinson-Wood, 2014). Suboptimal resistance strategies include emotional eating that correspond to weight gain, substance use, dependence upon others for validation, and/or unprotected sex, which increases risk for contracting sexually transmitted diseases.…”
Section: Resistance Theorymentioning
confidence: 99%
“…Suboptimal resistance is associated with short-term and/or pleasure inducing strategies (e.g., comfort eating and drinking) that offer immediate gratification and are soothing, but do not serve people well in the long run. Specifically, suboptimal resistance is associated with increased vulnerability to and poor health outcomes, such as obesity, diabetes, heart disease, and addiction (Martin, Boadi, Fernandes, Watt, & Robinson-Wood, 2013; Robinson & Ward, 1991; Robinson-Wood, 2014). Suboptimal resistance strategies include emotional eating that correspond to weight gain, substance use, dependence upon others for validation, and/or unprotected sex, which increases risk for contracting sexually transmitted diseases.…”
Section: Resistance Theorymentioning
confidence: 99%
“…Contributing to these stressors are the following: the absence of support that was present in their home countries, language barriers, the devaluation of their credentials, job inequalities, economic insecurity, lack of access to social networks, and changes to traditional gender roles which put these women at increased risk for IPV. Martin, Boadi, Fernandes, Watt, and Robinson-Wood (2013) found that Black women's experiences of depression are caused by systemic racism, micro-aggressions, poverty, cultural socialization, obesity, diabetes, and exposure to interpersonal and community violence. Bukowski, Hampton, Escobar-Viera, Sang, Chandler and Henderson (2019) found that the factors which were significantly correlated with symptoms of depression for Black transgender women (BTW) included IPV, physical and verbal violence, social support, gender identity, sex work, level of education, employment status, re-lationship status, and homelessness in the previous year.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The shelter in place mandates led to social isolation, which triggered feelings of loneliness, anxiety, and depression among the women. Black women are more likely to experience depression because of the intersections of poverty, racism, sexism, social health difficulties, and cultural socialization practices (Martin et al, 2013). Social isolation was an added layer.…”
Section: Narrative 2: Case Managermentioning
confidence: 99%